2021
DOI: 10.1007/s10157-021-02052-5
|View full text |Cite
|
Sign up to set email alerts
|

Intra-body dynamics of d-serine reflects the origin of kidney diseases

Abstract: Introduction d-Serine, present only in trace amounts in humans, is now recognized as a biomarker of chronic kidney disease (CKD). CKD is heterogeneous in its original kidney diseases, whose diagnoses require kidney biopsy. In this study, we examined whether the intra-body dynamics of d-serine, indexed by its blood and urinary levels, reflects the origin of kidney diseases. Methods Patients with six kinds of kidney disease undergoing kidney biopsy were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…For the development of new therapies, it is necessary to investigate the characteristics of the patient group showing treatment resistance more broadly. For example, it is expected that performing whole-exosome analysis of miR-NAs [25] or further profiling of kidney biomarkers such as d-amino acids [26][27][28], long-term undetected enantiomers of amino acids, will not only lead to the discovery of useful novel biomarkers, but also elucidate the mechanism of treatment resistance.…”
Section: Discussionmentioning
confidence: 99%
“…For the development of new therapies, it is necessary to investigate the characteristics of the patient group showing treatment resistance more broadly. For example, it is expected that performing whole-exosome analysis of miR-NAs [25] or further profiling of kidney biomarkers such as d-amino acids [26][27][28], long-term undetected enantiomers of amino acids, will not only lead to the discovery of useful novel biomarkers, but also elucidate the mechanism of treatment resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size calculation was performed on the basis of a previous study (15). Suppose the plasma level of d- serine was 2.8, 2.3, 2.8, and 1.5 μ M for patients with IgAN, MCD, and DN and normal participants, respectively; therefore, the number needed for a one-way ANOVA F test for group effect was 11 per group.…”
Section: Methodsmentioning
confidence: 99%
“…Studies based on 2D-HPLC revealed that D-serine reflects kidney function and disease activity 9,10 . A previous study also revealed that the levels of D-serine in blood and urine are also useful in the diagnosis of the origin of kidney diseases 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, D-Ser has been recently highlighted as a promising biomarker for evaluating kidney functions [1,[13][14][15]. In chronic kidney disease, D-Ser, D-Asn, and D-Pro levels are increased compared with healthy people, being strongly correlated with kidney function (glomerular filtration rate), while D-Asp and D-Pro may indicate the copresence of diabetes [16].…”
Section: Introductionmentioning
confidence: 99%